`f(x)=(1-4x-x^2)(x^2-4)`

To take the derivative of the given function, apply the power rule which is
`(u*v)'=v*u'+u*v'` .

So let,

`u=1-4x-x^2`
and `v=x^2-4`

Then, take the derivative of u and v to get u' and v'.

`u'=-4-2x`
and `v'=2x`

And, plug-in u,v, u' and v' to the formula of product rule.

`f'(x)=(x^2-4)(-4-2x) + (1-4x-x^2)(2x)`

Then, expand.

`f'(x)= -4x^2 -2x^3+16+8x+2x - 8x^2-2x^3`

Combine like terms.

`f'(x) = -4x^3-12x^2+10x+16`

**Hence, the derivative of the given function is
`f'(x)=-4x^3-12x^2+10x+16` .**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.